Osman's dream : the story of the Ottoman Empire, 1300-1923 - Finkel, Caroline (New York : Basic Books, 2006)
The Ottoman empire was one of the largest and most influential empires in world history. Its reach extended to three continents and it survived for more than six centuries, but its history is too often colored by the memory of its bloody final throes on the battle-fields of World War I. [This book is] for the general reader. [In the book, the author] recounts the story of the Ottoman Empire from its origins in the thirteenth century through its destruction in the twentieth. According to the Ottoman chronicles the first sultan, Osman, had a dream in which a tree emerged fully formed from his navel "and its shade encompassed the world"--Symbolizing the vast empire he and his descendants were destined to forge. His vision was soon realized - at its height, the Ottoman realm extended from Hungary to the Persian Gulf, from North Africa to the Caucasus. A multitude of religions flourished within its frontiers." With World War I, the Empire collapsed, and European colonial powers carved up former Ottoman lands. Their actions haunt us still - from the Balkans to Baghdad, the Ottoman sultanate once ruled over regions which are now amongst the most troubled on earth. In [the book, the author] narrates the dramatic history of this vast empire that shaped the modern world.-Dust jacket. Includes bibliographical references (p. 610-641) and index
First among equals -- A dynasty divided -- An imperial vision -- Sultan of the faithful -- Possessor of the kingdoms of the world -- The sedentary sultan -- Government by faction -- Revenge of the pashas -- Rule of the grandees -- The empire unravels -- The perils of insouciance -- The power of the provinces -- From the 'New Order' to the 'Re-ordering' -- A crisis of identity -- The Islamic empire -- The storm before the calm -- Sultans of the Ottoman Empire
Originally published: London : John Murray Publishers, 2005
Includes bibliographical references (pages 610-641) and index
Keywords: Turkey -- History -- Ottoman Empire, 1288-1918